Sequence Analysis of Putative potB, potC, and potD Genes from Serratia rubidae - SONY SUHANDONO; RASI FITRIA; ERNAWATI ARIFIN GIRI RACHMAN (Microbiology Indonesia, 2010)
Amplification of putative potBCD genes from Serratia rubidae was conducted by PCR using a pair of primers FERC and RERC. A fragment with ~1800 bp size was ligated to pGEM-T Easy vector then cloned to competent Escherichia coli DH5α. The recombinant plasmid was sequenced using SP6, T7 and two internal primers, FPC and RPC. A sequence similarity search and analysis was performed with the BLASTN program. The sequence was found to have 83% similarity to potABCD genes from E. coli. Those genes encoded a spermidine-preferential uptake system that consists of four kinds of protein: PotA is a membrane-associated ATPase, PotB and PotC are transmembrane proteins that form channels, and PotD is a periplasmic substrate-binding protein. Alignment analysis showed that the isolated clone consisted of potB (partial), potC (full length) and potD (partial). The sequences for potBCD genes from S. rubidae are not available in the NCBI database. Furthermore, we have submitted this sequence, potBCD from S. rubidae, on GeneBank with Acc. number FJ447342.